Walter Ruttmann and the cinema of multiplicity : Avant-Garde, advertising, modernity - Cowan, Michael J., 1971- (Introduction : avant-garde, advertising and the managing of multiplicity -- Absolute advertising : abstraction and figuration in Ruttmann's animated product advertisements (1922-1927) -- The cross-section : images of the world and contingency management in Ruttmann's montage films of the late 1920s (1927-1929) -- Statistics and biopolitics : conceiving the national body in Ruttmann's hygiene films (1930-1933) -- "Überall Stahl" : forming the new nation in Ruttmann's steel and armament films (1934-1940) -- Afterword : of good and bad objects., 2014)
A key figure in early avant-garde cinema, Walter Ruttmann was a pioneer of experimental animation and the creative force behind one of the silent era's most celebrated montage films, Berlin: Symphony of a Great City. Yet even as he was making experimental films, Ruttmann had a day job. He worked regularly in advertising -and he would go on to make industrial films, medical films, and even Nazi propaganda films. Michael Cowan offers here the first study of Ruttmann in English, not only shedding light on his commercial, industrial, and propaganda work, but also rethinking his significance in light of recent transformations in film studies. Cowan brilliantly teases out the linkages between the avant-garde and industrial society in the early twentieth century, showing how Ruttmann's films incorporated and enacted strategies for managing the multiplicities of mass society. This book has won the Willy Haas Award 2014 for its outstanding contribution to the study of German cinema.